Ectoparasite Infestation on Beef Cattle (Bos Indicus) in Kendit Sub-District, Situbondo District - Nizar Bachrudin Prihandono; Endang Suprihati; Lilik Maslachah; Poedji Hastutiek; mufasirin mufasirin (Journal of Parasite Science (JoPS), 2021)
The purpose of this study was to determine the type and percentage of ectoparasites attacking the cattle cow in the Kendit Sub-District, Situbondo District. The research was conducted from July to September 2020 with 100 samples of cow taken. The identification of ectoparasites was carried out at The Laboratory of the Animal Health Center of Situbondo Regency. This study was survey with a cross-sectional design. This study found several ectoparasites of the type of flies that infested the cattle cow: Musca domestica 29.20%, Haematobia irritans 58.96%, Stomoxys calcitrans 2.82%, Tabanus rubidus 0.42%, Tabanus megalops 0.56%, Hippobosca maculata 0.14%. In addition, this study also found ectoparasites of fleas that attacked the cattle cow, among others Bovicola bovis 2.12%, and Haematopinus eurysternus 5.78%. In this study, the dominant type of fly ectoparasite was Haematobia irritans 58.96% and the dominant ectoparasite from flea was Haematopinus eurysternus 5.78%. The suggestions for this research were this research should be continued with a longer time, the fishing method must be more varied because the more fishing methods used, the higher diversity results and it is advisable to maintain cage sanitation, improve maintenance management, and the cleanliness of cattle sheds surroundings to maintain cattle condition.